1993
DOI: 10.1136/gut.34.4.470
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of upper gastrointestinal vascular ectasias: long term results.

Abstract: Forty one patients with bleeding vascular ectasias of the upper gastrointestinal tract who required blood transfusion were treated with endoscopic Nd:YAG laser photocoagulation and followed for 34 months (median). Four distinct groups of patients were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 16 publications
0
49
0
4
Order By: Relevance
“…All series have confirmed the efficacy of this endoscopic thermal therapy by reducing or abolishing the need of blood transfusions in about 50% to 80% of cases, with a mean of 3 treatment sessions (range 1-10) [50][51][52][53] . The most serious complication described after laser therapy, even if rare, is represented by gastric perforation.…”
Section: Endoscopic Treatmentmentioning
confidence: 78%
See 1 more Smart Citation
“…All series have confirmed the efficacy of this endoscopic thermal therapy by reducing or abolishing the need of blood transfusions in about 50% to 80% of cases, with a mean of 3 treatment sessions (range 1-10) [50][51][52][53] . The most serious complication described after laser therapy, even if rare, is represented by gastric perforation.…”
Section: Endoscopic Treatmentmentioning
confidence: 78%
“…However, Bernstein and co-workers presented a case-report of a multifocal gastric cancer developed after repeated sessions of laser therapy over a five-year period [57] . Other important disadvantages of laser endoscopic therapy are the high cost and the need of a long training period, since most severe complications, such as perforation and death, happen more frequently when the endoscopist is not sufficiently skilled with the procedure [51,54] . Argon plasma coagulation (APC) is a noncontact technique with a controllable depth of coagulation (0.5-3 mm).…”
Section: Endoscopic Treatmentmentioning
confidence: 99%
“…As mentioned above, one patient did suffer a contained perforation, but given his two prior left gastric artery embolizations, the presence of gastric necrosis, and the location of the perforation, it is likely that his prior arterial embolizations were causal. However, since there is a previous report of gastric perforation from laser therapy, 16 which occurred primarily with the authors' initial use of the laser and was thought to be due to an excessively high-power setting, we are not able to definitively determine whether the laser therapy also contributed to this adverse outcome.…”
Section: Discussionmentioning
confidence: 69%
“…5,[13][14][15][16][17] In this series, we report six patients who were successfully treated, as evidenced by a decline in the number of packed red blood cells transfused, stabilization of the hematocrit, and lack of clinical signs of gastrointestinal bleeding, even when other therapies directed at GAVE failed to stop the bleeding. One patient required a gastrectomy because of ischemic gastric necrosis from angiographic transarterial embolization.…”
Section: Discussionmentioning
confidence: 97%
“…Clinical trials of endoscopic treatment in these patients have shown decreased transfusion requirements and increasing hemoglobin values. These did not reach statistically significant levels in some studies due to the small numbers of patients treated [32,[36][37][38][39][40][41].…”
Section: Gastrointestinal Involvementmentioning
confidence: 99%